Characterization of Novel Formazan Derivative and Study its Activity of Antihyperglycemic - Hasanain Gomhor Jasim (Al-Qadisiyah Journal of Pure Science, 2017)
In the present research, a 1-[4-((E)-((Z)-(phenylimino) (3,4,5-trihydroxyphenyl) methyl)diazenyl) phenyl] ethanone, (a Formazan Derivative) was synthesized by the condensation of Schiff base (5-[(phenylimino)methyl]benzene-1,2,3-triol) and diazonium salt of 4-amino acetophenone. The Schiff base 5-[(phenylimino)methyl]benzene-1,2,3-triol was itself synthesized by the condensation of aniline with 3,4,5-trihydroxybenzaldehyde. All the reaction were monitored and purity was determined on TLC, and spots were visualized by exposing the dry plates in iodine vapours. The synthesized formazan derivative has been characterized by CHN, UV-Vis, IR spectral data and melting points.The study was conducted to evaluate hypoglycemic effect of the synthesized formazan derivative on blood glucose level following oral administration to normal and alloxan treated rabbits. The rabbits are divided into control and treatment groups every group considered from six rabbits. The hypoglycemic effect of synthesized formazan derivative was studied in both types of rabbits. Group I was control group and received orally 3 ml of distilled water only. The groups II was treatment group and received orally with 150 mg/kg of synthesized formazan derivative dissolved in 3 ml of distilled water. Group III was treatment group too and received orally with 300 mg/kg of synthesized formazan derivative dissolved in 3 ml of distilled water.The synthesized formazan derivative is recorded excellent hypoglycemic effect in the blood glucose level . The cellular toxicity of synthesized formazan derivative was studied and showed it is nontoxic.